Biology and Ecology of Irukandji Jellyfish (Cnidaria: Cubozoa) - Gershwin, L.; Richardson, A.; Winkel, K.; Fenner, P.; Lippmann, J.; Hore, R.; Avila-Soria, G.; Brewer, D.; Kloser, Rudy; Steven, A.; Condie, S. (2013)
Irukandji stings are a leading occupational health and safety issue for marine industries in tropical Australia and an emerging problem elsewhere in the Indo-Pacific and Caribbean. Their mild initial sting frequently results in debilitating illness, involving signs of sympathetic excess including excruciating pain, sweating, nausea and vomiting, hypertension and a feeling of impending doom; some cases also experience acute heart failure and pulmonary oedema. These jellyfish are typically small and nearly invisible, and their infestations are generally mysterious, making them scary to the general public, irresistible to the media, and disastrous for tourism. Research into these fascinating species has been largely driven by the medical profession and focused on treatment. Biological and ecological information is surprisingly sparse, and is scattered through grey literature or buried in dispersed publications, hampering understanding. Given that long-term climate forecasts tend toward conditions favourable to jellyfish ecology, that long-term legal forecasts tend toward increasing duty-of-care obligations, and that bioprospecting opportunities exist in the powerful Irukandji toxins, there is a clear need for information to help inform global research and robust management solutions. We synthesise and contextualise available information on Irukandji taxonomy, phylogeny, reproduction, vision, behaviour, feeding, distribution, seasonality, toxins, and safety. Despite Australia dominating the research in this area, there are probably well over 25 species worldwide that cause the syndrome and it is an understudied problem in the developing world. Major gaps in knowledge are identified for future research: our lack of clarity on the socio-economic impacts, and our need for time series and spatial surveys of the species, make this field particularly enticing. © 2013 Elsevier Ltd.